2012
DOI: 10.7309/jmtm.17
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Near Eye Tool for Refractive Assessment (NETRA) – Pilot Study

Abstract: Background: Uncorrected-refractive-error (URE) is the leading cause of global vision impairment (VI); 122.5 million people are estimated VI from URE. NETRA is a $30USD clip-on application for smartphones. Purpose: To validate the NETRA as an alternative to subjective refraction for potential use in resourcepoor countries. Methods: NETRA uses a pinhole mask attached to a smartphone displaying a spatially resolved pattern to the subject. Refractive error is estimated by the patient subjectively aligning patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 7 publications
0
24
0
1
Order By: Relevance
“…However, in a recent study on 34 eyes, the M measured with the mobile phone refractometer was found to agree within 0.25 D of the SR in only 15% of the measured eyes. 23 There are several areas in which the QS could be improved. The range of the current prototype is limited to subjects with an M of greater than or equal to j6.0 D of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study on 34 eyes, the M measured with the mobile phone refractometer was found to agree within 0.25 D of the SR in only 15% of the measured eyes. 23 There are several areas in which the QS could be improved. The range of the current prototype is limited to subjects with an M of greater than or equal to j6.0 D of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Smartphones are also being utilized for retina imaging with an indirect lens and the built-in camera [26]. Assessment of refraction with a pinhole adopter attached to a smartphone is also another example to mention [27].…”
Section: Mobile Health Technologies and Screeningsmentioning
confidence: 99%
“…Так, у світовому масштабі рефракція залишається основною причиною всіх порушень зору. Для вирішення цієї проблеми, в рамках виконання програми NETRA (Near Eye Tool for Refractive Assessment) був розроблений оптичний пристрій, пристосований для використання із смартфоном, щоб дозволити виконувати суб'єктивне автоматич-не дослідження [32].…”
Section: медична інформатика медична інформатика та інженеріяunclassified